Sago Festival Development Strategy through a Community-Based Tourism Approach in Sebangun Village, Sambas - Trisnawati, Hikmah; Fatihah, Nur Astri; Pahima, Pahima; Risa, Risa (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Since its establishment in 2021, the Sago Festival in Sebangun Village, Sambas Regency, has evolved into an annual cultural event that simultaneously celebrates local heritage and promotes community-based economic empowerment. This study aims to formulate strategic directions for enhancing the festival’s development within the framework of Community-Based Tourism (CBT), ensuring its sustainability and optimizing socio-economic outcomes. A qualitative descriptive approach was employed, integrating field observations, in-depth interviews, and literature analysis. The collected data were systematically examined using the SWOT analytical framework. The findings indicate that the festival’s primary strengths include active community participation, well-established local branding, and the abundance of sago resources. Conversely, internal weaknesses consist of venue instability, declining sago tree availability, and limited promotional efforts. External opportunities—such as collaboration with governmental and academic institutions and the expansion of digital media—further enhance the festival’s development prospects. Drawing from these insights, five strategic directions are proposed: (1) establishing a permanent festival venue; (2) implementing sustainable sago cultivation programs; (3) strengthening digital marketing and destination branding; (4) fostering inter-village and stakeholder collaboration; and (5) enhancing youth engagement through cultural education and capacity-building initiatives. Collectively, these strategies emphasize the significance of participatory management and sustainable resource utilization in advancing cultural tourism. Accordingly, the Sago Festival represents a promising model for community-based cultural tourism development in Sambas.